Peran pelatihan dan efikasi diri terhadap minat berwirausaha dalam upaya peningkatan produktivitas kelompok tani di desa Putat Nutug Ciseeng, Bogor - Noor, Laili Savitri; Badriah, Badriah; Hendratni, Tyahya Whisnu (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This study aims to determine the effect of training and self-efficacy on interest in entrepreneurship to increase the productivity of farmer groups in Putat Nutug Village, Ciseeng, Bogor Regency. The population in this study were members of a farmer group of 150 people. Determination of the number of samples using the Slovin formula totaling 60 respondents, with a sampling technique using purposive sampling. The data analysis technique used structural equation modeling Partial Least Square (SEM-PLS). The results showed no direct effect of training on business interest and no direct influence of business interest on productivity. Training has a direct effect on productivity, self-efficacy on business interest, and self-efficacy on productivity. There is no effect of training on productivity through interest in entrepreneurship, and there is no effect of self-efficacy on productivity through interest in entrepreneurship.